The Multicultural Liaison Officers' Perspective in Assessing Refugee Children in the Schools - Beglari, Afarin; Thai, Huong (Refuge: Canada's Journal on Refugees, 2000)
Any assessment, psychological, educationalor speech and language, even in thenative language, may pose many challengesfor refugee children and theirfamilies in the schools. The MulticulturalLiaison Officers are based at theschools to help families in dealing with anew educational systern. One of the areasthe MLOs play a major role is in assistingthe schools in assessing students. Thisarticle examines the involvement of theMulticultural Liaison Oficers and theirperspectives on assessing refugee childrenwith disabilities as well as some ofthe obstacles and possibilities the familiesand the professionals face in dealingwith this process.